In-phasic cytosolic-nuclear Ca2+ rhythms in suprachiasmatic nucleus neurons - Hiro, Sota; Kobayashi, Kenta; Nemoto, Tomomi; Enoki, Ryosuke (Frontiers in Neuroscience, 2023)
The suprachiasmatic nucleus (SCN) of the hypothalamus is the master circadian clock in mammals. SCN neurons exhibit circadian Ca2+ rhythms in the cytosol, which is thought to act as a messenger linking the transcriptional/translational feedback loop (TTFL) and physiological activities. Transcriptional regulation occurs in the nucleus in the TTFL model, and Ca2+-dependent kinase regulates the clock gene transcription. However, the Ca2+ regulatory mechanisms between cytosol and nucleus as well as the ionic origin of Ca2+ rhythms remain unclear. In the present study, we monitored circadian-timescale Ca2+ dynamics in the nucleus and cytosol of SCN neurons at the single-cell and network levels. We observed robust nuclear Ca2+ rhythm in the same phase as the cytosolic rhythm in single SCN neurons and entire regions. Neuronal firing inhibition reduced the amplitude of both nuclear and cytosolic Ca2+ rhythms, whereas blocking of Ca2+ release from the endoplasmic reticulum (ER) via ryanodine and inositol 1,4,5-trisphosphate (IP3) receptors had a minor effect on either Ca2+ rhythms. We conclude that the in-phasic circadian Ca2+ rhythms in the cytosol and nucleus are mainly driven by Ca2+ influx from the extracellular space, likely through the nuclear pore. It also raises the possibility that nuclear Ca2+ rhythms directly regulate transcription in situ.